هجرة الأدمغة الأفريقية وآثارها على البلدان الأفريقية - Abdul Hakim, Abdullah; Cisse, Ahanadou (2017)
The migration of highly educated and skilled individuals to abroad has become one of the prominent challenges facing by African countries. This phenomenon has caused the loss of human resource, professionals and skillful people who can contribute to the development of their country. The purpose of this research is to discuss the phenomenon of African brain drain in order to identify factors that cause them leaving their countries, to discover the implications of this phenomenon on the African countries in terms of economy, education and social, as well as to suggest the solutions for this phenomenon.To achieve this purpose, the researchers used descriptive analytical method. This study found that the most important factors that lead the African brains migrate outside their countries because the lack of financial resources, difficult economic condition, unstable political and social situation that constitute conflicts in the most African countries. Besides, the African brains feel that they are sequestered in their own country and start to find a new living situation that can promise them freedom, stability and peace. The implications of African brain drain are both, positive and negative. The positive implications are; improving their competency as they continuously involve in knowledge and research activities in the developed countries and enjoying secure and better living. The negative implications are; affecting the development of the African countries economically and socially as well as affecting human development in the African continent. This study suggest that the African countries have to improve their local environments to avoid the brain drain phenomenon and take care of their academic staff at universities. Further research should be conducted on the factors lead to the African brain drain and find the effective solutions.